Activated PIK3CD drives innate B cell expansion yet limits B cell–intrinsic immune responses - Wray-Dutra, Michelle N. (J Exp Med, 2018)
Activated PI3K-delta syndrome (APDS) is an immunodeficiency caused by gain-of-function mutations in PIK3CD. This disease exhibits complex immune phenotypes including increased IgM, recurrent infection, and impaired vaccine responses. To better understand the impact of B cells in this disease, we generated an inducible model of the common APDS mutation (hPIK3CD-E1021K; referred to as aPIK3CD) and intercrossed these mice with B cell–specific Cre models. Mb1-aPIK3CD mice exhibited bone marrow B lymphopenia and, conversely, expansion of the peripheral innate B1a and MZ B cell compartments. aPIK3CD B cells manifest increased pS6 and increased survival at several stages, without alterations in cycling, and baseline increases in plasma cells, natural IgM, and IgG3. Finally, Mb1-aPIK3CD mice exhibited blunted T cell–independent immune responses, and both AID- and CD21-aPIK3CD mice displayed reduced class-switched antibodies following T cell–dependent immunization. Thus, aPIK3CD alters B cell development and function and is counter-productive during immune responses, providing insight into B cell–intrinsic contributions to the APDS phenotype.